Aptamer based diagnosis of crimean-congo hemorrhagic fever from clinical specimens - Tahmineh Jalali (Nature Portfolio, 2021)
Abstract Crimean-Congo hemorrhagic fever (CCHF) is an acute viral zoonotic disease. The widespread geographic distribution of the disease and the increase in the incidence of the disease from new regions, placed CCHF in a list of public health emergency contexts. The rapid diagnosis, in rural and remote areas where the majority of cases occur, is essential for patient management. Aptamers are considered as a specific and sensitive tool for being used in rapid diagnostic methods. The Nucleoprotein (NP) of the CCHF virus (CCHFV) was selected as the target for the isolation of aptamers based on its abundance and conservative structure, among other viral proteins. A total of 120 aptamers were obtained through 9 rounds of SELEX (Systematic Evolution of Ligands by Exponential Enrichment) from the ssDNA aptamer library, including the random 40-nucleotide ssDNA region between primer binding sites (GCCTGTTGTGAGCCTCCTAAC(N40)GGGAGACAAGAATAAGCA). The KD of aptamers was calculated using the SPR technique. The Apt33 with the highest affinity to NP was selected to design the aptamer-antibody ELASA test. It successfully detected CCHF NP in the concentration of 90 ng/ml in human serum. Evaluation of aptamer-antibody ELASA with clinical samples showed 100% specificity and sensitivity of the test. This simple, specific, and the sensitive assay can be used as a rapid and early diagnosis tool, as well as the use of this aptamer in point of care test near the patient. Our results suggest that the discovered aptamer can be used in various aptamer-based rapid diagnostic tests for the diagnosis of CCHF virus infection.